Modulation of TLR4/NFκB Pathways in Autoimmune Myocarditis - Livia Interdonato; Daniela Impellizzeri; Ramona D'Amico; Marika Cordaro; Rosalba Siracusa; Melissa D'Agostino; Tiziana Genovese; Enrico Gugliandolo; Rosalia Crupi; Roberta Fusco; Salvatore Cuzzocrea; Rosanna Di Paola (MDPI AG, 2023)
Myocarditis is an inflammatory and oxidative disorder characterized by immune cell recruitment in the damaged tissue and organ dysfunction. In this paper, we evaluated the molecular pathways involved in myocarditis using a natural compound, Coriolus versicolor, in an experimental model of autoimmune myocarditis (EAM). Animals were immunized with an emulsion of pig cardiac myosin and complete Freund's adjuvant supplemented with mycobacterium tuberculosis; thereafter, Coriolus versicolor (200 mg/Kg) was orally administered for 21 days. At the end of the experiment, blood pressure and heart rate measurements were recorded and the body and heart weights as well. From the molecular point of view, the Coriolus versicolor administration reduced the activation of the TLR4/NF-κB pathway and the levels of pro-inflammatory cytokines (INF-γ, TNF-α, IL-6, IL-17, and IL-2) and restored the levels of anti-inflammatory cytokines (IL-10). These anti-inflammatory effects were accompanied with a reduced lipid peroxidation and nitrite levels and restored the antioxidant enzyme activities (SOD and CAT) and GSH levels. Additionally, it reduced the histological injury and the immune cell recruitment (CD4+ and CD68+ cells). Moreover, we observed an antiapoptotic activity in both intrinsic (Fas/FasL/caspase-3) and extrinsic (Bax/Bcl-2) pathways. Overall, our data showed that Coriolus versicolor administration modulates the TLR4/NF-κB signaling in EAM.